1997
DOI: 10.1046/j.1365-2761.1997.d01-115.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic similarity of iridoviruses from Japan and Thailand

Abstract: Iridovirus infection causes serious economic damage in marine cultured fish in Japan, Hong Kong and Singapore, and the incidence of this disease has been increasing. Iridovirus of sea bass from offshore Hong Kong was isolated to determine the genetic similarities of the causative agents. The genomic DNA of iridovirus was purified and cloned. Four DNA clones were randomly chosen and sequenced to generate primers for the polymerase chain reaction (PCR). Corresponding DNA fragments of iridoviruses from sea bass f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 0 publications
0
35
0
2
Order By: Relevance
“…Each viral isolate was inoculated onto confluent monolayers of CRF-1 cells in three replicate 25-cm 2 flasks as described above. DNA extraction from these iridovirus isolates was performed by a proteinase K lysis method (30). Briefly, the infected cell culture including supernatant was centrifuged at 50 ϫ g for 20 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each viral isolate was inoculated onto confluent monolayers of CRF-1 cells in three replicate 25-cm 2 flasks as described above. DNA extraction from these iridovirus isolates was performed by a proteinase K lysis method (30). Briefly, the infected cell culture including supernatant was centrifuged at 50 ϫ g for 20 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The incidence of iridovirus infection has been increasing among cultured fish in Japan (29,30). In addition, genetic and phenotypic iridovirus variants suggest the presence of diverse variants in this virus group (16).…”
mentioning
confidence: 99%
“…DNA was extracted from ALIV and from DGIV by the Proteinase K lysis method (Sambrook et al 1989, modified by Miyata et al 1997). Approximately 10 to 50 mg of spleens excised from naturally iridovirus-infected dwarf gourami or pieces of the body of naturally iridovirus-infected lampeye was homogenized in a 0.5 ml aliquot of the 1× Proteinase K lysis buffer (50 mM Tris-HCl, 10 mM EDTA, 2% (w/v) sodium dodecyl sulfate, 10 µg ml -1 Proteinase K) in a glass homogenizer.…”
Section: Methodsmentioning
confidence: 99%
“…RSIV has caused serious fish losses, which result in severe economic losses. The presence of the virus in fish has been reported from Asian regions including Korea, Japan, China, Taiwan and Thailand (Inoue et al, 1992;Chua et al, 1994;Kasornchandra and Khongpradit, 1997;Miyata et al, 1997;Jung and Oh, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…E-mail: tklee@kiost.ac. Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License and caused huge economic losses (Inoue et al, 1992;Chua et al, 1994;Kasornchandra and Khongpradit, 1997;Miyata et al, 1997;Jung and Oh, 2000). The RSIV was first isolated from the cultured red sea bream Pagrus major in 1992 (Imajoh et al, 2007;Inoue et al, 1992;Caipang et al, 2006), and has been found to infect more than 30 species of cultured fishes since then.…”
Section: Introductionmentioning
confidence: 98%